A Systematic Review of Principal-Agent Problems in Free School Meal Policy Implementation in Southeast Asia - Tobroni; Aminullah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Free school meal programs have become a flagship social-welfare policy across Southeast Asia, yet their implementation routinely encounters quality, targeting, and accountability failures once national authority is delegated to thousands of dispersed local operators. This study addresses the urgent but underexamined question of how the implementation gap in such programs can be systematically explained through Principal-Agent Theory (PAT). Using a systematic literature review of 24 academic and credible institutional sources published largely within the last decade, supplemented by classic agency-theory references, this study synthesizes evidence from Indonesia's Makan Bergizi Gratis (MBG), Thailand's decades-old school lunch program, and the Philippines' DepEd School-Based Feeding Program (SBFP). Sources were identified through structured keyword searches, screened for relevance to policy-implementation and principal-agent content, and thematically analyzed across three PAT dimensions: information asymmetry, moral hazard/agency cost, and monitoring and incentive design. The findings show that despite different national contexts, all three countries display a recurring pattern: extensive delegation to frontline operators under conditions of limited direct observability, followed by recurrent agency failures (food poisoning, mistargeting, procurement corruption), prompting principals to construct layered, costly monitoring and sanction mechanisms. The study concludes that PAT offers a parsimonious and empirically robust lens for diagnosing implementation failure in decentralized welfare delivery and proposes a comparative framework that can guide more cost-effective oversight design for free school meal policies across the region.